Optimization of inorganic phosphate solubilization by Pseudomonas fluorescens and Bacillus sp. isolated from wheat rhizospheric soil - Chibani, Hiba Rahman; Bellahcene, Miloud; Bouznad, Ahcene; Djibaoui, Rachid; Hamoum, Hakim (My University, 2017)
Phosphate solubilizing bacteria play a vital role in soil fertility. They are used to promote the growth of a large group of plants. The aim of this work was to evaluate the bacterial isolates’ capacity to release inorganic phosphate and optimizing their solubilization. Different culture media, nitrogen source and carbon source were used under varying culture conditions for optimizing solubilization of phosphate by two bacteria isolated from saline soil Pseudomonas fluorescens and Bacillus sp. Optimization of growth conditions was also tested using different incubation periods, temperature and pH. The comparison of amounts of phosphorus released by the isolates in different liquid cultures showed that the best solubilization was obtained in NBRIP medium for both Pseudomonas and Bacillus with quantities of 65.619 µg/mL and 560.667 µg/mL of free phosphorus, respectively. Glucose was found to be the best source of carbon for solubilization of phosphate by the two isolates. The effect of the variation of nitrogen source in the medium allowed to select ammonium sulfatas the most favorable nitrogen source for both bacterial isolates. The results showed that the pH = 5 and the incubation temperature of 30°C are optimal conditions for phosphate solubilization bybacterial isolates. The study of the effect of incubation time led to select the 6th day of incubation as an optimal time for phosphate solubilization by the two isolates.
Keywords: Bacillus sp., Phosphate solubilizing bacteria, Pseudomonas fluorescens, Optimization, Tricalcium phosphate